2009
DOI: 10.1002/dneu.20701
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐dependent regulation of TrkB isoforms in rodent visual cortex

Abstract: Within primary visual cortex (V1), brain-derived neurotrophic factor (BDNF) signaling through its high-affinity receptor TrkB is important for normal development and experience-dependent plasticity. TrkB is expressed in several alternatively spliced isoforms, including full-length TrkB (TrkB.FL), and several truncated isoforms (TrkB.T1, TrkB.T2, and TrkB.T4) that lack the intracellular tyrosine kinase domain. These isoforms are important components of BDNF signaling, yet little is known about the developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 58 publications
(97 reference statements)
3
23
0
Order By: Relevance
“…Visual experience after DR normalized the expression of these proteins. Our findings are in accordance with those of previous studies, showing reduced visual acuity after DR during the critical period (Fagiolini et al, ; Prusky et al, ) accompanied by reduced BDNF expression within the visual cortex of rats (Bracken and Turrigiano, ), and that environmental enrichment during DR has a compensatory effect (Pham et al, ; Cancedda et al, ; Sale et al, ). It has been further shown that high‐frequency rTMS applied to conscious rats is able to raise cortical BDNF levels in adult rats (Gersner et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Visual experience after DR normalized the expression of these proteins. Our findings are in accordance with those of previous studies, showing reduced visual acuity after DR during the critical period (Fagiolini et al, ; Prusky et al, ) accompanied by reduced BDNF expression within the visual cortex of rats (Bracken and Turrigiano, ), and that environmental enrichment during DR has a compensatory effect (Pham et al, ; Cancedda et al, ; Sale et al, ). It has been further shown that high‐frequency rTMS applied to conscious rats is able to raise cortical BDNF levels in adult rats (Gersner et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, a growing list of CNS molecules are emerging as substrates for MMPs, such as β-dystroglycan, zona occludens-1, and myelin basic protein (13). A selective increase or decrease in cell surface presentation of truncated receptors, internalization of ligand-bound receptors, and stimulus-dependent TRKB processing by agents such as zinc are some known pathways through which BDNF is trapped, salvaged, or scavenged (14,15). Such mechanisms may predominate in situations requiring a rapid and reversible alteration of TRKB on neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for BDNF/TrkB functions in pyramidal neurons (Bracken and Turrigiano, 2009) and their developing spines is also abundant (Tyler and Pozzo-Miller, 2003; Chakravarthy et al, 2006; Tanaka et al, 2008). Furthermore, it has been established that PSD-95 at synapses is crucial to spine maturation (Kim and Sheng, 2004; van Zundert et al, 2004) and that BDNF-TrkB signaling plays a central role in facilitating glutamate synapse stabilization/maturation through the PSD-95 scaffold (Ji et al, 2005; Yoshii and Constantine-Paton, 2007, 2010).…”
Section: Discussionmentioning
confidence: 99%